The Routledge handbook of historical linguistics - Bowern, Claire 1977-; Evans, Bethwyn (Routledge, 2015)
"The Routledge Handbook of Historical Linguistics provides a survey of the field covering the methods which underpin current work; models of language change; and the importance of historical linguistics for other subfields of linguistics and other disciplines. Divided into five sections, the volume encompass a wide range of approaches and addresses issues in the following areas: historical perspectives; methods and models; language change interfaces; regional summaries. Each of the thirty-two chapters is written by a specialist in the field and provides: a[n] introduction to the subject; an analysis of the relationship between the diachronic and synchronic study of the topic; an overview of the main current and critical trends; and examples from primary data. The Routledge Handbook of Historical Linguistics is essential reading for researchers and postgraduate students working in this area" --